Factors Affecting Purchase Intention of Indian Consumers towards Green Products - Roshni Agarwal (International Journal of Advanced Science and Technology, 2020)
This research study reflects on green marketing, it also sheds light on customer perceptions and the desire to buy eco-friendly goods. It has been a major problem for the mitigation of waste and environmental degradation. A number of studies have been carried out on eco-friendly marketing investigating the issue and the interaction between consumer behaviour and consumer behavior of eco-friendly goods. Through the insights given by professionals, competent and experienced experts, businesses have evolved to incorporate the idea of green marketing in the development of environmentally friendly goods and this formed the basis of my study.Methodology/Design - A questionnaire was given to elicit the views of people, how the marketing-mix elements (4P) and WOM surrounding green attitudes impacts their views and the purchasing aim of eco-friendly goods. Convenient sampling was done to collect the data. A total of 120 responses were inspected. First, Reliability Analysis was conducted to remove the inaccurate responses and questions. Then, Dimension reduction was done so as to group alike variables. Lastly, multiple Regression was done on these factors so as to identify the priority of all the factors in order to focus on these factors only while marketing green products.Findings – Total of 5 factors could explain 62% variability. Also, one of these factors, Purchase Frequency, was found to be the most significant after Multiple Regression was conducted.Originality/value – Although many studies have been conducted on green marketing, but this study in Indian perspective gives a new angle by diversifying factors in marketing terms.